2022
DOI: 10.21814/rlec.4059
|View full text |Cite
|
Sign up to set email alerts
|

The Ladder of Power: Science Communication and Citizen Science

Abstract: On March 28, 2022, the Journal of Science Communication published a special issue on participatory science communication featuring 15 papers and essays. The Journal of Science Communication special issue sparked a debate among the four editors over the wording of the call for papers. What is the difference between “participatory science communication” and “citizen science”? Are they different points along a continuum stretching from “simple” to “more involved”? Does “citizen science” incorporate “participatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…It was shown that CS projects lead by professional scientists (as well as by NGOs) tend to not perform to engagement in a participatory way in what we called communication preparedness through digital channels. This resonates with previous findings in the literature of Science Communication [Kouper, 2010;McClain, 2017] as well as in CS [Golumbic et al, 2017], further confirming that the challenges and limits of public engagement are not yet overcome or solved [Riesch et al, 2013] even with a promising engaging approach such as CS, further confirming the common challenges with Science Communication [Gascoigne et al, 2022].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It was shown that CS projects lead by professional scientists (as well as by NGOs) tend to not perform to engagement in a participatory way in what we called communication preparedness through digital channels. This resonates with previous findings in the literature of Science Communication [Kouper, 2010;McClain, 2017] as well as in CS [Golumbic et al, 2017], further confirming that the challenges and limits of public engagement are not yet overcome or solved [Riesch et al, 2013] even with a promising engaging approach such as CS, further confirming the common challenges with Science Communication [Gascoigne et al, 2022].…”
Section: Discussionsupporting
confidence: 88%
“…The same seems to apply to science communication as well [Riesch, Potter & Davies, 2013]. As recently considered, the two, CS and Science Communication, share the same challenges and, perhaps face similar limits as well as opportunities [Gascoigne, Metcalfe & Riedlinger, 2022].…”
Section: Introductionmentioning
confidence: 77%
“…Lipinski (2015) recommends that discussions (and thus communication) within projects between experts and non-experts should be horizontal. Gascoigne et al (2022) believe that this suggests a more participatory form of science communication where citizens are involved at each stage of the project right up to policy co-production. In this way, science communication combined with CS, and implemented at multiple levels, involves a shift of power and the emergence of responsible research and innovation, and thus promotes the transition from "science in society" to "science with and for society" (Gascoigne et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this sense, CS offers great potential for science communication, because in CS projects research and communication are not separate processes, but closely intertwined (Wagenknecht et al, 2021). Through interactions between scientists and citizens, the target audience essentially becomes involved in the communication process itself (Giardullo et al, 2023), thus moving communication beyond mere dissemination of project results (Gascoigne et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, science communication is a key component for successfully recruiting, retaining, and motivating citizen scientists (Baruch et al, 2016;Wagenknecht et al, 2021). Since communication strategies shape the expectations associated with CS in general and specific projects in particular, they need to be well thought out and appropriate for the level of participation (Gascoigne et al, 2022). For those CS projects created by academic scientists, the success of the scientific research endeavor depends on citizens' involvement -that is, a sufficient number of citizens must be willing to participate and engage in the project tasks.…”
Section: Introductionmentioning
confidence: 99%